PERUBAHAN TERJADINYA PUNCAK PASANG SURUT SUNGAI BARITO AKIBAT PEMANASAN GLOBAL - Holdani Kurdi; Ulfa Fitriati; M. Ainun Najib; Aulia Isramaulana (Universitas Lambung Mangkurat, 2019)
Regional development engineering in coastal areas, tidal land reclamation, delta area reclamation and port planning, tidal knowledge is very important. Tides mainly occur due to the gravitational forces of the moon, sun, and other planets. The influence of different gravitational forces can be predicted precisely because the rotation and revolutionary movements of the earth, moon, sun, and other planets take place with very high order. The tidal period every day is mainly determined by the rotation of the earth with a 24-hour period. Influence of the sun even though its attraction is only half that of the lunar pull, its influence should not be ignored As understood months around the earth with a period of about 29.5 days. When the position of the moon-earth-sun is in line, the tidal forces of the sun and moon strengthen each other. At that time spring tide occurred. Whereas if the sun-earth forms an angle of 90 degrees, then the minimum tides occur (neap tide). The two conditions are about 7 days old, according to the moon's revolution. Because of the influence of the inertia of the mass of water, the spring and neap tide occur between one and three days after these extreme conditions occur. In short-term studies often researchers take extreme conditions, namely during the tidal peak and peak tide (spring tide), because it does not require a long time compared to researching during a longer tide period. The research approach that will be carried out is whether the tide and peak peaks still occur 1-3 days after the full moon and the dead moon, whether there is a change in the height of the tide and ebb during a certain period due to global warming. As a result of global warming, it is also an effect on the water level of the Barito River. There was a decrease in the maximum water level which previously was around 3 m, now only around 2 m, the minimum water level previously around 2 m was now below 1 m. This will affect the hydrotopographic conditions of tidal swamp land, land that was previously type A can change to type B and so on. The highest tides on the Barito River often occur in the dead months, namely the 1st and 29th of the Hijri.